Reproductive health counseling on sexual behavior in adolescents in landslide disaster Prone Areas, Sirnaresmi Village, Sukabumi Regency - Haryani, Hana (Bhakti Sabha Nusantara, 2022)
Population quality of life, especially reproductive health, declines after landslides. Any reproductive health stimulation is compared to ordinary material content and reproductive health. Adolescents sometimes lack sexuality-related knowledge, and peer information might be inaccurate, thus misinformation may lead them to make mistakes. West Java's Sirnaresmi Village, Sukabumi Regency, is prone to landslides. Teenagers live there. The purpose of implementing this counseling activity on Sexual Behavior is to optimize the knowledge and understanding of adolescents in landslide-prone areas of Sirnaresmi Village, Sukabumi Regency about reproductive health related to sexual behavior. The method of implementing the activity includes three stages, namely planning, implementation, and evaluation. The activity was carried out for 3 months. The participants who took part in this activity were as many as 20 participants. The result of the implementation of activities is an increase in adolescents' knowledge and understanding of reproductive health related to sexual behavior.